Analog and Digital Games as a Pedagogical Tool in the Teacher Training Context - Maria do Céu Ribeiro (Research in Social Sciences and Technology- OpenED Network, 2019)
This article focuses on analog and digital game play and the challenges it poses to future teachers in an educational context. For that, a review of the literature on the subject was made, addressing the theories of Piaget and Vygotsky. We refer to the game as a pedagogical resource, its relation to the teaching-learning process, and its role in stimulating the multiple intelligences referenced by the psychologist Howard Gardner. Structurally framed by this theoretical framework, we developed this study in an integrated internship context in a classroom of the First Cycle of Basic Education, with 20 children ages 9 and 10. In order to carry out this research, we developed teaching-learning experiences that allowed us to answer the following question: How do the different game supports (analog/digital) motivate children to the teaching-learning process? In order to answer this question, we have outlined the following objectives: i) to understand if the type of support in which children play influences learning; ii) develop activities in contexts, using games (analog and digital); (iii) understand, to what extent, playing games encourages the development of multiple skills. The study is part of a descriptive, interpretive, and reflexive process, framed in a qualitative approach. For data collection, we used participant observation, observation log grids, field notes, photographic records, and interviews with the children. After analyzing the data, these tend to reveal, among other aspects, a remarkable improvement in motivation of children, perceiving that the game is an excellent teaching/learning strategy that allows the development of social and communication skills of children, predisposing the child for learning. As far as the type of game support is concerned, we found that although digital is more appealing to children born in the Digital Age, we verified that both the game in analog and digital support, when properly integrated into the educational action, are also promoters of meaningful and lasting learning.